Immunization Status Analysis Based On Knowledge Characteristics And Family Support - Hamid Muhammed A; Alex (Journal of Applied Nursing and Health, 2022)
Background: Immunization is one of the preventative measures to spread the disease to other regions, which has proven to be very cost-effective. Good knowledge and support from families in implementing immunizations will improve the immunization status of children. The purpose is to know whether there is a relationship between basic immunization status based on knowledge and family support. Methods: The design used in the study is cross-sectional. The population is all mothers with babies. The sample size was 53 respondents using the Conventional Sampling technique. The independent variable of research is family knowledge and support. The dependent variable is immunization status. Data were collected using a questionnaire; then, data were analyzed using logistic regression tests with a significance level of α ≤ 0.05. Results: The results showed that almost half of the respondents had sufficient knowledge of 26 respondents (49.1%), sufficient family support of 21 respondents (39.6%), and the complete immunization status of 34 respondents (64.2%). The results obtained by Overall Statistics with a significance value of (p) 0,000 which means that family knowledge and support affect immunization status. This means there is a Relationship between Basic Immunization Status Based on Characteristics of Knowledge and Family Support. Conclusion: There is a relationship between primary immunization status based on the characteristics of knowledge and family support